2006
DOI: 10.1249/01.mss.0000222840.58767.40
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Physical Fitness and Physical Activity from Youth to Adulthood in Females

Abstract: In Flemish females, anthropometric and fitness characteristics demonstrate higher levels of stability from adolescence to middle adulthood than physical activity. Weight status during adolescence is indicative of adult weight status, and a pattern of less activity rather than activity tends to continue from youth to adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
69
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 16 publications
14
69
1
7
Order By: Relevance
“…Tracking was more variable (0.25 -0.85 in Canadians and 0.55 -0.76 in Madeira's youngsters) for waist circumference (Katzmarzyk et al 1999). Similar tracking coefficients have been reported for Belgians (Beunen et al 1992;Hulens et al 2001;Matton et al 2006), English (Power et al 1997), Swiss (Gasser et al 1995) and US-citizens (Casey et al 1992). In this last study the correlations for females approached zero when longer periods (childhood to 40 or 50 years) were considered.…”
Section: Tracking Of Body Fatness 63supporting
confidence: 83%
“…Tracking was more variable (0.25 -0.85 in Canadians and 0.55 -0.76 in Madeira's youngsters) for waist circumference (Katzmarzyk et al 1999). Similar tracking coefficients have been reported for Belgians (Beunen et al 1992;Hulens et al 2001;Matton et al 2006), English (Power et al 1997), Swiss (Gasser et al 1995) and US-citizens (Casey et al 1992). In this last study the correlations for females approached zero when longer periods (childhood to 40 or 50 years) were considered.…”
Section: Tracking Of Body Fatness 63supporting
confidence: 83%
“…As with the correlation analyses, stronger regression coefficients were found for males compared with females in three of the four studies. For example, in the three remaining studies with baseline ages between 15 and 19 years and 11 to 18 years follow-up β values ranged from 0.08 to 0.69 in males and from no association to 0.49 in females [18,[29][30][31][32].…”
Section: Associations Between Physical Activity Levels At Baseline Anmentioning
confidence: 99%
“…The remaining studies reported activity in terms of sports participation. In the Leuven Longitudinal Study on Lifestyle, Fitness and Health [18] those 'less active' at 16 years were 2.0 (95% CI 0.9-4.3) times likely to be 'less active' 24 years later. The Northern Finland 1966 birth cohort (NFBC) [36,37] and Cardiovascular Risk in Young Finns (CVRYF) [29][30][31][32] reported their analyses by gender.…”
Section: The Probability Of Being Physically Active At Follow-up Accomentioning
confidence: 99%
See 2 more Smart Citations